The impact of government efficiency and macroeconomics on public debt: empirical evidence from advanced economies and emergingeconomies - Wei, Ni Soh; Muhamad, Haslinah; Ong, Tze San (Universiti Putra Malaysia Press, 2021)
This research investigates the empirical relationship of government efficiency, corruption, and inflation regarding public debt between advanced and emerging economies. Random effects estimation is used to analyse a sample of 40 countries. The analysis results show that corruption and inflation in advanced economies have a significant and positive effect on public debt. Corruption affects public debt to increase, but on the flip side, inflation affects public debt to decrease. In emerging economies, the results show a positive impact of government efficiency on public debt. Hence, government efficiency will be considered an obstacle when a policy initiated to reduce public debt. Meanwhile, policymakers should take note countries’ corruption and inflation rates when formulating policies to reduce public debt in advanced economies.